Uji Potensi Cracker dengan Tepung Kulit Bawang Merah (Allium ascalonicum) sebagai Pangan Fungsional berAntioksidan dan Antihiperkolesterolemik - Rista Anggriani; Rizki Khoirun Nisa; Susi Oxyvia Rosenansi; Marcya Hulwatul Purtanti; Warkoyo Warkoyo (Food Technology and Halal Science Journal, 2020)
Diet is one of the causes of obesity and obesity, for example by consuming foods with high cholesterol levels such as fast food or fried foods, so it is necessary to find alternative non-fried processed products that have functional properties. Cracker as a non-fried processed product is fortified with shallot skin flour which has antioxidant activity. This research purpose is to determine the effect of adding shallot skin flour (3, 5, 10%) to the cracker against total cholesterol reduction after 7 days of consumption. This research used laboratory experimental methods with pre post test design with control group. Each group consisted of 5 Wistar rats (2 control groups and 4 treatment groups) so total Wistar rats used were 30 rats. In addition, antioxidant activity was also tested. The results indicated that cracker in the P3 formula (10% fortification of shallot skin flour) had high antioxidant activity of 68.90% and was able to decrease cholesterol with the highest precentage reduction of 10% after 7 days of consumption. This cracker can be categorized as a functional food which has high antioxidants and antihypercholesterolemic activity.